Adenoid facies: a long-term vicious cycle of mouth breathing, adenoid hypertrophy, and atypical craniofacial development - Zhang, Jiaqi; Fu, Yongwei; Wang, Lei; Wu, Geng (Frontiers in Public Health, 2024)
Adenoid hypertrophy (AH) is characterized by pathological hyperplasia of the nasopharyngeal tonsils, a component of Waldryer’s ring, which represents the first immune defense of the upper respiratory tract. The pathogenic factors contributing to AH remain to be comprehensively investigated to date. Although some studies suggest that environmental exposure to smoke and allergens, respiratory tract infections, and hormonal influences likely contribute to the development of AH, further research is necessary for fully elucidating the effects of these factors on the onset and progression of AH. AH is the most common cause of airway obstruction in the pediatric population, with a prevalence rate of 49.7%, and is frequently accompanied by various comorbidities. These patients often present with distinctive dental characteristics, including increased overjet, posterior crossbite, a high palatal plane, narrow dental arches, and facial features characterized by disproportionate alterations in facial height, commonly referred to as “adenoid facies.” Individuals with adenoid facies frequently display abnormal breathing patterns, especially mouth breathing. The present review summarizes the findings of research articles sourced from PubMed, IEEE, and Web of Science over the last 20 years up to September 2024. Several high-quality studies screened using the PICOPS framework reported that perioral muscle dysfunction, dental and skeletal malocclusions, and upper airway obstruction caused by AH are interdependent issues and mutually exacerbate one another. The review summarizes the potential associations and mechanisms linking AH, mouth breathing, and the subsequent development of adenoid facies in children.